Service Performance Evaluation of ITS Library Institution Repository Website - Eva Mursidah; Davi Wahyuni; Yeni Anita Gonti; Eko Budi Raharjo (JPUA: Jurnal Perpustakaan Universitas Airlangga: Media Informasi dan Komunikasi Kepustakawanan, 2022)
The ITS library as a unit that supports the ITS industrial revolution 4.0 strategy must make improvements to the application of information technology services to users. The ITS library repository website as a portal for storing scientific works of the ITS academic community is one of the information technology services that is often used by the ITS academic community (siva), but there has been no development for more than 5 years. For this reason, it is necessary to research evaluating the service quality of the ITS library repository website using webqual 4.0, which includes 3 (three) dimensions, namely: usability, information quality, and service interaction quality. The method used is a survey of distributing questionnaires to ITS final semester students who use the repository's independent upload service. As many as 100 students use the repository's independent upload service, then an IPA analysis (importance performance analysis) is carried out to determine the level of user satisfaction. The measurement results of the evaluation of the ITS Library repository website show a gap of -0.7, meaning that user satisfaction with the ITS Library repository website has not yet been achieved, while the IPA matrix diagram shows 2 (two) service indicators that are prioritized for quality improvement, namely interaction with the ITS repository website, which is safe from viruses and hackers when accessed via a PC or smartphone, and a quick search menu (title, author, supervisor, department) that gives inaccurate search results.